2005
DOI: 10.1073/pnas.0500778102
|View full text |Cite|
|
Sign up to set email alerts
|

The Arabidopsis SUMO E3 ligase SIZ1 controls phosphate deficiency responses

Abstract: Plants sense phosphate (Pi) deficiency and initiate signaling that controls adaptive responses necessary for Pi acquisition. Herein, evidence establishes that AtSIZ1 is a plant small ubiquitin-like modifier (SUMO) E3 ligase and is a focal controller of Pi starvation-dependent responses. T-DNA insertional mutated alleles of AtSIZ1 (At5g60410) cause Arabidopsis to exhibit exaggerated prototypical Pi starvation responses, including cessation of primary root growth, extensive lateral root and root hair development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
632
1
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 555 publications
(658 citation statements)
references
References 40 publications
21
632
1
4
Order By: Relevance
“…Interestingly, SIZ1, PHR1, and PHR2, which are located upstream of OsIPS1, were slightly downregulated after 10 days under −P stress in roots and shoots and slightly upregulated at 1 d after recovery in roots, an expression pattern which was in contrast with that of OsIPS1. These genes were previously reported to be upregulated slightly under −P stress based on qRT-PCR analysis and northern analysis (Rubio et al 2001;Miura et al 2005). This apparent discrepancy indicates that a more detailed analysis of gene expression during different stages of stress via mRNA-Seq could be useful in detecting subtle changes in gene expression.…”
Section: Promoter Analysis and Alternative Splicing Isoforms Of Respomentioning
confidence: 87%
See 1 more Smart Citation
“…Interestingly, SIZ1, PHR1, and PHR2, which are located upstream of OsIPS1, were slightly downregulated after 10 days under −P stress in roots and shoots and slightly upregulated at 1 d after recovery in roots, an expression pattern which was in contrast with that of OsIPS1. These genes were previously reported to be upregulated slightly under −P stress based on qRT-PCR analysis and northern analysis (Rubio et al 2001;Miura et al 2005). This apparent discrepancy indicates that a more detailed analysis of gene expression during different stages of stress via mRNA-Seq could be useful in detecting subtle changes in gene expression.…”
Section: Promoter Analysis and Alternative Splicing Isoforms Of Respomentioning
confidence: 87%
“…The regulation system for the-P signaling pathway in plants has been proposed using studies in Arabidopsis and involved the sumoylation of the MYB transcription factor PHR1 by a small ubiquitin-like modifier SIZ1 in a process dependent on E3 ligase (Miura et al 2005;Gojon et al 2009). Located downstream of PHR1, miR399 and IPS1 (induced by phosphate starvation1) are specifically induced by −P stress.…”
Section: Introductionmentioning
confidence: 99%
“…©2011 KSMCB 1 mental responses, including heat shock, pathogen defense, drought and cold tolerance, ABA signaling, flowering, and phosphate deficiency (Catala et al, 2007;Jin et al, 2008;Lee et al, 2007;Miura et al, 2005;2009;Saracco et al, 2007;Yoo et al, 2006). Recently, van den Burg et al (2010) reported that AtSUMO3 acted downstream of SA accumulation, while involvement of AtSUMO1 and AtSUMO2 has been reported in suppressing SA accumulation.…”
Section: Molecules and Cellsmentioning
confidence: 99%
“…However, many aspects of biological function and regulation in plants, including the nature of SUMO target proteins, remain poorly defined. To date, a small number of SUMO target proteins have been uncovered in the form of seven genuine Arabidopsis proteins, MYB30, GTE3/5, PHR1, ICE1, ABI5 and FLD, that harbor sumoylation consensus motifs (Garcia-Dominguez et al, 2008;Jin et al, 2008;Miura et al, 2005;2009;Okada et al, 2009). In addition, very recent are reports about systematic approaches using yeast two-hybrid assays and affinity enrichment methods with mass spectrometry for mapping SUMO target proteins (Elrouby and Coupland, 2010;Miller et al, 2010).…”
Section: Molecules and Cellsmentioning
confidence: 99%
“…Conversely, the overexpression of SUMO isoforms results in growth-defective plants (Budhiraja et al 2009;van den Burg et al 2010). Although there are several SUMO proteins, only two SUMO E3 ligases have been characterized in Arabidopsis-SIZ1 and MMS21/HPY2 (Huang et al 2009;Ishida et al 2009;Miura et al 2005). The siz1 and mms21/hpy2 mutants exhibit pleiotropic phenotypes that involve ABA (abscisic acid), biotic, and Copyright © 2014 The Japanese Society for Plant Cell and Molecular Biology abiotic stress (heat, cold, salt, and drought) responses, nutrient availability, plant development, and flowering (Catala et al 2007;Chen et al 2011;Jin et al 2008;Lee et al 2007;Miura et al 2007b;Miura et al 2011a;Miura and Ohta 2010;Miura et al 2011b;Park et al 2011;Yoo et al 2006).…”
mentioning
confidence: 99%